Role of the Neutrophil-Lymphocyte Ratio in the Differential Diagnosis of Exudative Pleural Effusion (Clinics, 2016)
OBJECTIVES: Pleural effusion is a common diagnostic and clinical problem. The differential diagnosis of pleural effusion may be difficult and may require several procedures, including invasive ones. Certain studies have investigated biochemical parameters to facilitate the diagnosis of exudative pleural effusion; however, it remains a challenging problem in clinical practice. We aimed to investigate the potential role of the neutrophil-lymphocyte ratio, which can be easily obtained by determining the cell count of the pleural fluid, in the differential diagnosis of exudative pleural effusion. METHODS: Records from patients who underwent thoracentesis and pleural fluid analysis between May 1, 2013, and March 1, 2015, were obtained from the electronic database of our hospital. The patients who met the inclusion criteria were divided into five groups according to their diagnosis: malignant pleural effusion, para-malignant pleural effusion, para-pneumonic effusion, tuberculosis-related effusion or other. The neutrophil-lymphocyte ratio value was calculated by dividing the absolute neutrophil count by the absolute lymphocyte count. The patient groups were compared according to the given parameter. RESULTS: A total of 465 patients who met the inclusion criteria among 1616 patients with exudative pleural effusion were included in the study. The mean neutrophil-lymphocyte ratio value was significantly lower in tuberculosis-related pleural effusion compared to malignant, para-pneumonic and para-malignant effusions (p=0.001, p=0.001, p=0.012, respectively). The areas under the curve for tuberculosis pleurisy compared to malignant, para-pneumonic and para-malignant effusions were 0.38, 0.36, and 0.37, respectively. Lower cut-off values had higher sensitivity but lower specificity for tuberculosis pleurisy, while higher cut-off values had higher specificity but lower sensitivity for this condition. CONCLUSION: The pleural fluid neutrophil-lymphocyte ratio, which is an inexpensive, reproducible, and easily calculated hematological parameter, may facilitate the differential diagnosis of pleural effusion.